The Effect of Data Protection, Digital Literacy and Cyber Security on the Security Risk of Social Engineering-Based Cyber Threats in E-Wallet Users (Study on Millennial Generation E-Wallet Users in Bandar Lampung City) - Kristianto, Aditia Dwi; Kurniawan, Muhammad; Etika, Citra (ProBisnis : Jurnal Manajemen, 2025)
The security risk of cyber threats on e-wallets can be influenced by data protection, digital literacy and cyber security among e-wallet users. This study aims to determine and explain whether Data Protection, Digital Literacy and Cyber Security affect the Security Risk of cyber threats in millennial generation e-wallet users in Bandar Lampung City. The method used is quantitative research method, using questionnaire data. The data analysis method used is multiple linear regression models. The sampling technique used accidental sampling techniques and data testing using validity tests, reliability tests, classical assumption tests with a 5% significance level, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, t tests, f tests, and coefficient of determination tests. The results of this study in the (t) test show that the Data Protection variable has a significance of 0.001. This means that the tcount is 3,280 and the significance level is 0.001 (0.001 <0.05). The Digital Literacy variable has a tcount of 5,132 with a significance of 0.000. The Cyber Security variable has a tcount of 4,134 with a significance of 0.000. Based on the results of the simultaneous test (F test) shows a significance value of 0.00 <0.05 and an Fcount value of 118,930. the conclusion of this study, the Data Protection variable affects Security Risk, this is because, the higher the data protection, the higher the security risk when using an e-wallet. The Digital Literacy variable has an effect on Security Risk, this is because the increase in digital literacy affects the increase in security risks of using e-wallets. Cyber Security variables affect Security Risk, this is because the higher cyber security affects the high security risks of e-wallet users.